Measuring the performance of MAIDAM Kuala Terengganu project / Rosma Nuraini Mazelan - Mazelan, Rosma Nuraini (2010)
The purpose of study was to measuring the performance of MAIDAM as an institution which fully responsible for the economic development of Islam in Terengganu. From studies, it appears that the projects undertaken by the MAIDAM has a high potential for economic development in Terengganu. Although the projects developed by MAIDAM has a high potential, but they face many problems such as site development, capital, management is not effective, and others. Research carried out to move some solutions to the problems faced by the MAIDAM. The projects have been carried out need the best governance to enhance and streamline the management of the economy, especially the Malay Muslims.